Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia, dan Kebijakan Pemerintah terhadap Kemiskinan di Sumatera Barat - Farel Pratama Putra; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This Study aims toi see (1) the effect of economic growth on poverty in Westi Sumatera (2) the effect ofi the human development index on poverty in West Sumatra1 (3) the effect ofi government policies on poverty in West Sumatra1. This type of research is descriptive and associative. The data used in thisii study is secondary data fromii West Sumatra in thei from ofi panel data fromi 2015 to 2019 and data obtained from thei Central Statistics Agency (BPS) of West Sumatra. This type of research is descriptive and associative. The data used in thisi study isi Indonesian secondary data in the formi of panel data fromi 2010 to 2019i and this data was obtained fromi the official institutions of thei Ministry of Finance and thei Central Statistics Agency. The method used is panel analysis of regression data which is processed using Eviews. The results showed that economic growth had a positive and significant effect on poverty in West Sumatra Regency/City with, the Human Development Index had a negative and significant effect on Poverty in West Sumatra Regency/City with a, Government Policy (BANSOS PIP) has a negative and insignificant effect on poverty in the Regency/City of West Sumatra.